Directorial Vision and its Relation to Scenographic Proposal in the Iraqi Theater Show- The Play of Darkness -A Model: رامي سامح زكي (Al-Academy, 2019)
The increase of the scenographic designer role on account of the character of the director in the Iraqi theater constituted a clear phenomenon that has been manifested in many shows, which necessitated a stance on the nature of this relation and delimiting the work space for each one of them inside the theater show. The research focuses on determining the work relation between the directorial vision and the scenographic proposal in the Iraq theater show. The research is divided into four chapters, the first one addressed the methodological framework, where the research problem was stated in the following question (has the scenographic designer been able through his scenographic proposal to remove the director from his position being the owner of the overall vision and the first creator of the theatrical show?). The research importance lies in the fact that the researcher diagnosed those working in the two fields of direction and scenography as the most prominent beneficiaries from the research. The research aims at determining the kind of creative relationship between the director and the scenography designer in the Iraqi theater show. The researcher put limits for the research and identified the terms used and then defined them procedurally. The second chapter (theoretical framework) consists of two sections: the first addressed (the development of the concept of direction in theatrical show industry), while the second addressed (the visual composition between the director and scenography designer). The researcher presented the most prominent indicators resulting from the theoretical framework. The third chapter has been dedicated for the research procedures. The research population consists of the play (the Darkness) which is intentionally chosen to be representative of the study population using the descriptive method in the analysis of the sample. The researcher specified the analysis tools and then analyzed the sample. The fourth chapter includes the results based on indicators resulting from the theoretical framework. The most important results are as follows: scenography came to dominate the operational system of the directorial vision in most of the visual discourse area through exaggeration and the technical review, which led it to be overwhelming over the pillars of the directorial vision. The research ended with a list of references and sources used by the researcher in this study and an abstract in English